Factors determining welfare of the child in Malaysian civil law of custody: an analysis of decided cases - Abd Malek, Normi (UKM Press, 2011)
The welfare or interest of the child is the paramount consideration in deciding disputes relating to custody. Several factors, such as wishes of both the child and parents, preservation of status quo and the age of the child, are usually taken into consideration in determining the interest of the child. The question arises as to how far wishes of the parents are considered by the court. Are the child's views followed in all situations? Is the mother always the best in care taking? Another issue is whether to separate the children or not (if there is more than one child in the dispute) in deciding custody disputes. How does conduct of the disputed parties contribute to the interests of the child? Shall the status quo be preserved at all times? Should 'physical, moral and emotional well being' factor be included in the statute? What is the role of a welfare officer in promoting the interests of the child? This article attempts to provide answers to the above questions and at the same time suggestions will be made to improve the law, wherever appropriate